Corporate Finance and Environmental, Social, and Governance (ESG) Practices - Ştefan Cristian Gherghina (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This special issue comprises 12 papers published in the Special Issue entitled "Corporate Finance and Environmental, Social, and Governance (ESG) Practices", addressing a wide range of topics related to the following: corporate reporting (sustainability reporting; environmental accounting information disclosure and financial risk; compulsory preliminary profit and loss disclosure and stock prices; capital expenditure and ESG disclosure; and International Financial Reporting Standards (IFRS) disclosure and the cost of equity capital); essential drivers of enterprise value (the mediating role of ESG scores in the association between board gender diversity and firm values; promoters' holdings, institutional holdings, the dividend payout ratio and firm value; leverage and firm values; sustainable finance, capital and firm values); the impact of agency issues, as well as ESG, socially responsible investing (SRI), ethical investing, and impact investing, on corporate performance; and perspectives concerning the way the automobile sector is evolving to produce zero-emission vehicles.
Keywords: 330; ESG; SRI; bibliometric analysis; publication metrics; debt ratio; firm value; net profit margin; sales; profitability; electromobility risk; rare metals; environmental protection; costs of automotive transformation; cost of equity capital; IFRS; European firms; STOXX Europe 600; GMM-system; capital expenditure; ESG disclosure; stakeholder theory; resource dependence theory; principal component analysis; sustainable finance; firm's value; institutional ownership; institutional holdings; promoters' holdings; dividend payout ratio; firm size; agency problem; agency cost; agency theory; bibliometric; business performance; corporate governance; compulsory disclosure; fair disclosure; preliminary earnings announcement; profit and loss structure change disclosure; gender diversity; Saudi Arabia; masculinity—feminist cultural dimension; environmental accounting; environmental accounting information disclosure; financial risk; sustainable companies; CSI; sustainability reporting; non-financial reporting; systematic review; sustainability accounting; legitimacy theory; n/a